Szekspir nasz powszedni albo praktyka sensownego czytania w szkole (dziś, tj. „w czasach zarazy cyfrowej” oraz relacji globalnych, a także niezależnie od jakichkolwiek plag czy kataklizmów) - Kłakówna, Zofia Agnieszka (Tematy i Konteksty, 2019)
The paper is based on the assumption that the contemporary educational system, including its general approach to literature, is characterized by being totally old-fashioned, and its results are completely opposite to what the authors of the relevant programmes hoped to achieve, and this is the reason why it desperately needs re-evaluating and revising. The text documents various motivations of interpreting William Shakespeare’s romantic comedy, The Tempest, as an example of a valuable and meaningful work of fiction. Thus ‘t is a good starting point for a constructive reflection on how to create conditions suitable for studying literature-based texts in the classroom as well as on teachers’ training which would respect both the up-to-date cultural context and the value of humanistic education, paramount for the development of human identity, and which is nowadays widely contested by the present interim economic and technical priorities.